CHARACTERISTICS OF UROLOGY PATIENTS TREATED BY STICHTING SAMENWERKING VLISSINGEN-AMBON (SSVA) IN HAULUSSY HOSPITAL 2017-2018 - Ebram Nainggolan; Jacky Tuamelly (Molucca Medica, 2022)
Introduction. BPH, Urolithiasis and UTI are often urology cases found in Indonesia. There is no epidemiological data about Urology Patients in Maluku Province. Some patients in the province were handled either through referral to other cities or rely on charity program (SSVA) because there was no Urologist available yet in the province. Aim. To understand the characteristics of urology patients treated by SSVA in Maluku Province, including age, gender, and diagnosis. Method. This descriptive study used retrospective data from the medical records of patients treated by the SVVA in Haulussy Hospital from 2017–2018. Results. From a total of 281 (100%) urology patients, there were 173 (61.65%) benign prostatic hyperplasia (BPH) cases, 52 (18.50%) nephrolithiasis cases, 20 (7.11%) urinary tract infection cases, 13 (4.62%) hydrocele cases, 9 (3.2%) vesicolithiasis cases, and 5 (1.77%) varicocele cases. The largest number of BPH patients was from 60-69 years old age group with a total of 71 (41.04%) patients, followed by 70-79 years old age group with a total of 45 (26.01%) patients. From a total of 52 nephrolithiasis patients, there were 28 (53.48%) male patients and 24 (46.15%) female patients, and according to patient age, the largest number was from the 40-59 years old age group with a total of 31 (59.62%) patients, followed by the 60-79 years old age group with a total of 11 (21.16%) patients. Conclusion. The largest number of urology patients treated by the SVVA were BPH patients, followed by nephrolithiasis and urinary tract infection patients. The age group that suffered the most from BPH are those aged 60-69 years. In nephrolithiasis patients, it was found that male patients were slightly more prevalent than female. The age group that suffered the most from nephrolithiasis are those aged 40-59 years. Keywords: Characteristics; Urology